Relationship on Timeliness of SPT Reporting and Reported Income in Accordance with Applicable Provisions on Taxpayer Compliance - Yenie Eva Damayanti; Ahmad Karim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Compliance is one of the important factors in increasing revenue from the tax sector. Indonesia’s low tax ratio is an indicator that there are still many taxpayers who do not comply with tax payments and reporting. The study examines how the relationship between the timeliness of SPT reporting and reported income in accordance with applicable regulations on taxpayer compliance. The method is causality research method. The population are registered taxpayers at the KPP North Malang area. The sampling uses convenience sampling method with a total of 75 respondents. The results of hypothesis testing with multiple linear analysis show that together there is a positive relationship between the timeliness of reporting tax returns and income reported in accordance with applicable regulations on taxpayer compliance. The results of the Spearman correlation test show that there is a significant relationship between the timeliness of reporting tax returns with taxpayer compliance and there is a significant relationship between reported income in accordance with applicable regulations and taxpayer compliance.